Kinematics on Handmade Rubber Car using Tracker Experiment Design in Learning Force and Motion - Muharam, Ghevira Syaharani Aulia; Prima, Eka Cahya; Winarno, Nanang; Riandi, Riandi (Jurnal Pendidikan Fisika Indonesia, 2024)
Experimental activity in learning science allows students to develop critical thinking, active learning, creativity, scientific, and collaboration skills. This study aims to create an alternative experimental design for learning force and motion, which analyzes the kinematics aspect of handmade rubber cars using Tracker. The method used is the R&D method with the ADDIE model to develop the experimental design on the material of force and motion for grade 7 junior high school students. The Tracker application was used to evaluate trial data on handmade rubber cars to calculate the acceleration, force, and time needed by the vehicle with varying the number of rubber turned. Then, to evaluate the experimental design, this study used a questionnaire instrument, and the experimental design was implemented in four classrooms of junior high school students in the seventh grade. The results were examined based on the percentage of students who answered each statement. The kinematics analysis of handmade rubber cars using Tracker shows that the more significant the number of turns given to the vehicle, the more acceleration and force decrease. Meanwhile, the car still travels longer when the number of rubbers turned is higher. This happened because the car took longer to reach maximum speed, and the rubber band detaches when more rubber is turned on. Moreover, the experimental activity of making handmade rubber cars using Tracker was well received by students, as seen from the response questionnaire scores, which were categorized as high. This study suggests that further research can implement different independent variables as the experiment design parameters based on this result. Teachers and other researchers can utilize the developed experimental design as an alternative strategy in learning force and motion topics.